Pengaruh Kualitas Jasa Perguruan Tinggi Swasta terhadap Loyalitas Mahasiswa - Albari Albari (Management Development Centre (MDC) Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2009)
The study focuses on the effects of service quality on private institutions of tertiary studies toward students’ trust and students’ loyalty. The service quality in education can be measured into soft attribute as well as hard attribute approaches.Using convenience sampling, the sample involved 288 Post Graduate Students. They represent from all Schools of Management at Private Institutions of Tertiary Studies in which they have Magister Management Program in Yogyakarta. The results show Soft Service Quality positively influence on Excellent Performance Perceptions and Trust. Meanwhile, Excellent Performance Perceptions positively influence on Trust, and Trust positively influence on Loyalty. When Trust as mediating, the study examines that Relationship Quality indirectly positively influence on Loyalty. Keywords: soft service quality, hard service quality, trust, loyalty.